POLITICAL COMPETITION AND LOCAL REVENUE: HOW ARE THEY RELATED? - Awaliyah, Isyatul Hazar; Martua, Aleknaek; Elvis, Elvis; Hayatuddin, Zulkifli (Fakultas Politik Pemerintahan, 2023)
Democracy today is very important because all citizens are given relatively equal rights in making decisions that can change their lives for the better. Some previous studies have shown that the amount of allocated funds distributed tends to correlate with areas that have been controlled by the party that is currently in control of the government. This study will focus on examining the impact of political concentration on the allocation of DAU and DAK, which will indirectly impact PAD. This research uses quantitative analysis of secondary data with the object of researching all districts and cities in Prov. Papua and Prov. West Papua in the period 2017-2021. The analytical method used in this research is multiple linear regression analysis. The results found in this study are that there is a positive correlation between HHI and DAU per capita and DAK per capita. However, in statistical testing, the effect of HHI does not appear to be significant on PAD per capita within a district/city area in Prov. Papua and Prov. West Papua.